Maternal Stress and the Future Child: Pathways Linking Prenatal Stress with Labor and Developmental Outcomes - N. Masiukovichi; W. M. Caudle; T. Masiukovichi; E. Nikoleishvili (European Scientific Journal, ESJ, 2026)
Introduction: Maternal stress during pregnancy is a key determinant of obstetric and neonatal outcomes, influencing both fetal development and maternal health. Psychosocial and biological stress pathways, particularly dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, and elevated cortisol are linked to adverse labor progression (including prolonged labor, obstetric complications) and neonatal outcomes (Apgar scores at 1 and 5 minutes, newborn anthropometrics). Understanding these mechanisms is essential for developing integrative maternal care strategies that mitigate stress-related risks. Objective: To assess the association between maternal stress during pregnancy, labor progression, and neonatal outcomes. Methods: A cross-sectional study was conducted among 398 pregnant women in Tbilisi, Georgia. A validated pregnancy-specific questionnaire was used to assess self-reported stress, and salivary cortisol was measured in a subgroup of 95 women reporting high stress. Labor characteristics and neonatal outcomes (Apgar scores at 1 and 5 minutes, newborn anthropometrics) were analyzed. Statistical analyses were performed using SPSS v.23.0. Results: Two groups were formed: the Study Group (n=172; stressed, with a subgroup of 95 women, showing elevated cortisol levels) and the Control Group (n=226; non-stressed). Delivery complications occurred in 51.9% of stressed women versus 26.6% of controls (p=0.001), with more than twice the odds of complications (OR = 2.21; 95% CI = 1.13–4.33; p = 0.021). Newborns of stressed mothers were twice as likely to have low 1-minute Apgar scores (OR = 2.12; p = 0.028). No significant difference was found in 5-minute Apgar scores (OR = 1.13; p = 0.257). Conclusions: Elevated maternal stress and cortisol levels were significantly associated with higher risks of delivery complications and reduced neonatal vitality at birth. These findings position maternal stress as a clinically relevant and modifiable determinant of intrapartum risk. The markedly higher rates of delivery complications and early neonatal compromise in stressed women support the integration of routine stress screening and psychosocial assessment into standard antenatal care. From a policy and practice perspective, targeted stress-reduction interventions—such as psychological counseling, social support programs, and stress-management strategies—should be incorporated into prenatal services to improve obstetric and neonatal outcomes. Future research should focus on evaluating the effectiveness of such interventions, identifying critical gestational windows of vulnerability, and clarifying the biological pathways linking maternal stress, cortisol dysregulation, and perinatal outcomes.